Screening for Colorectal Cancer: US Preventive Services Task Force Recommendation Statement - Davidson, Karina W; Barry, Michael J; Mangione, Carol M; Cabana, Michael; Caughey, Aaron B; Davis, Esa M; Donahue, Katrina E; Doubeni, Chyke A; Krist, Alex H; Kubik, Martha; Li, Li; Ogedegbe, Gbenga; et al. (JAMA : the journal of the American Medical Association, 2021)
Colorectal cancer is the third leading cause of cancer death for both men and women, with an estimated 52 980 persons in the US projected to die of colorectal cancer in 2021. Colorectal cancer is most frequently diagnosed among persons aged 65 to 74 years. It is estimated that 10.5% of new colorectal cancer cases occur in persons younger than 50 years. Incidence of colorectal cancer (specifically adenocarcinoma) in adults aged 40 to 49 years has increased by almost 15% from 2000-2002 to 2014-2016. In 2016, 26% of eligible adults in the US had never been screened for colorectal cancer and in 2018, 31% were not up to date with screening. To update its 2016 recommendation, the US Preventive Services Task Force (USPSTF) commissioned a systematic review to evaluate the benefits and harms of screening for colorectal cancer in adults 40 years or older. The review also examined whether these findings varied by age, sex, or race/ethnicity. In addition, as in 2016, the USPSTF commissioned a report from the Cancer Intervention and Surveillance Modeling Network Colorectal Cancer Working Group to provide information from comparative modeling on how estimated life-years gained, colorectal cancer cases averted, and colorectal cancer deaths averted vary by different starting and stopping ages for various screening strategies. Asymptomatic adults 45 years or older at average risk of colorectal cancer (ie, no prior diagnosis of colorectal cancer, adenomatous polyps, or inflammatory bowel disease; no personal diagnosis or family history of known genetic disorders that predispose them to a high lifetime risk of colorectal cancer [such as Lynch syndrome or familial adenomatous polyposis]). The USPSTF concludes with high certainty that screening for colorectal cancer in adults aged 50 to 75 years has substantial net benefit. The USPSTF concludes with moderate certainty that screening for colorectal cancer in adults aged 45 to 49 years has moderate net benefit. The USPSTF concludes with moderate certainty that screening for colorectal cancer in adults aged 76 to 85 years who have been previously screened has small net benefit. Adults who have never been screened for colorectal cancer are more likely to benefit. The USPSTF recommends screening for colorectal cancer in all adults aged 50 to 75 years. (A recommendation) The USPSTF recommends screening for colorectal cancer in adults aged 45 to 49 years. (B recommendation) The USPSTF recommends that clinicians selectively offer screening for colorectal cancer in adults aged 76 to 85 years. Evidence indicates that the net benefit of screening all persons in this age group is small. In determining whether this service is appropriate in individual cases, patients and clinicians should consider the patient's overall health, prior screening history, and preferences. (C recommendation).